Shapes of epitaxial gold nanocrystals on SrTiO3 substrates - Chen, P; Murugappan, K; Castell, MR (Royal Society of Chemistry, 2020)
Morphological control of gold nanocrystals is important as their catalytic and optical properties are highly shape dependent. In this paper we report the shapes of gold nanocrystals which deviate from the equilibrium Wulff shape due to the influence of the SrTiO3 single crystal substrates. The gold crystals are characterized by scanning tunneling microscopy (STM) and scanning electron microscopy (SEM). The nanocrystals have an equilibrium shape of a truncated octahedron with {111} and {001} facets. On all three substrate surfaces, i.e., SrTiO3(001)-(2 × 1), SrTiO3(001)-c(4 × 2), and SrTiO3(111)-(4 × 4) + (6 × 6), the height-to-width ratio of the gold crystals is not a constant as would be expected for equilibrium crystals, but instead it increases with crystal height. We propose that as the crystals increase in size, their aspect ratio heightens to relax the interfacial strain. The ratio between the {111} and {001} surface areas of our gold crystals is found to differ on the three substrates, which we speculate is due to the selective adsorption of surfactants on the {111} and {001} gold facets resulting from the different substrate surfaces. Reentrant facets of gold crystals that should be present according to their Wulff shape are not observed because these concave sites typically grow out due to kinetic considerations. This study demonstrates the significant effect of the crystal facet termination and surface reconstruction of an oxide substrate on the shape of supported gold nanocrystals.